2021
DOI: 10.3748/wjg.v27.i37.6290
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori in gastric cancer: Features of infection and their correlations with long-term results of treatment

Abstract: BACKGROUND Helicobacter pylori ( H. pylori ) is a spiral-shaped bacterium responsible for the development of chronic gastritis, gastric ulcer, gastric cancer (GC), and MALT-lymphoma of the stomach. H. pylori can be present in the gastric mucosa (GM) in both spiral and coccoid forms. However, it is not known whether the severity of GM contamination by various vegetative forms of H. pylori is associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 76 publications
0
9
0
Order By: Relevance
“…Helicobacter pylori is a class I carcinogen associated with GC ( 170 172 ). The overall survival of GC diagnosis is reported to be higher for patients with H. pylori infection ( 17 ).…”
Section: Effects Of H Pylori On Tumor Immunotherap...mentioning
confidence: 99%
“…Helicobacter pylori is a class I carcinogen associated with GC ( 170 172 ). The overall survival of GC diagnosis is reported to be higher for patients with H. pylori infection ( 17 ).…”
Section: Effects Of H Pylori On Tumor Immunotherap...mentioning
confidence: 99%
“…Studies have indicated that oral administration of Shenling Baizhu powder could reduce bacterial colony forming units in gastric ulcer caused by gastric acid by about 30 % [16] . The extracts of some traditional Chinese medicines have anti-inflammatory activity and can inhibit myeloperoxidase activity at the site of gastric ulcer.…”
Section: Groupmentioning
confidence: 99%
“…Chronic gastritis can progress sequentially to atrophic gastritis, when a loss of appropriate glands takes place; to intestinal metaplasia, when gastric mucosa further acquires intestinal features; to neoplastic stage without invasion, called dysplasia; and, finally, to gastric cancer [12,13]. A progression of gastric cancer might also be associated with H. pylori infection [14]. In a group of patients, infection with virulent H. pylori strains contributed to the development of gastric ulcer disease and MALT (mucosaassociated lymphoid tissue) lymphoma.…”
Section: Introductionmentioning
confidence: 99%